PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA GAME WORDWALL TERHADAP HASIL BELAJAR SISWA: Studi Eksperimen pada Materi Ekosistem Kelas V SDN Jenggrik 2 Tahun Ajaran 2024/2025 - Nursabila, Alma Fitri; Mahendra, Moefty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Wordwall educational games on the learning outcomes of fifth-grade students at SDN Jenggrik 2 in the ecosystem topic. The research was motivated by low student achievement and the limited use of interactive media in science learning. A quantitative approach with a quasi-experimental design was used. The sample consisted of 27 students in the experimental class and 29 students in the control class. The test instrument consisted of 10 multiple-choice questions that had been validated for reliability. The experimental class applied the PBL model integrated with Wordwall media throughout the learning process, while the control class used conventional lecture-based methods. Data were analyzed using an independent sample t-test with SPSS version 26. Results showed that the experimental class had a mean score of 75.19, higher than the control class with a mean of 62.1. The t-test showed a significance value of 0.001 < 0.05, indicating a significant difference between the two groups. It is concluded that the use of the PBL model assisted by Wordwall has a positive effect on improving student learning outcomes in ecosystem material.